Data generated for "Serial MRD assessment predicts relapse after transplantation in patients with myelodysplastic syndrome. - Tobiasson, Magnus; Institution for medicine Huddinge, Karolinska Institute; Department of hematology, Karolinska University Hospital (Karolinska Institutet, 2024)
The study has evaluated the association between measurable residual disease (MRD) determined using digital droplet PCR (ddPCR) and outcome after allogeneic stem cell transplantation for patients with myelodysplastic syndrome (MDS). The patient-specific mutations have been identified using next generation sequencing (NGS).

The dataset contains:
1. NGS data
2. MRD data
3. List of ddPCR-assays
4. Variants for ddPCR only identified at diagnosis
5. Variants of undetermined significance targeted by ddPCR
6. Regression analyses

Studien har utvärderat relationen mellan kvarvarande sjukdom (MRD) undersökt med digital droplet PCR (ddPCR) och utfall efter allogen stamcellstransplantation för patienter med myelodysplastiskt syndrom (MDS). De patient-specifika mutationerna har identifierats med en NGS-panel.

Följande data finns:
1, NGS-data
2. MRD-data
3. Lista på ddPCR-assays
4. Varianter för ddPCR bara identifierad vid diagnos
5. Varianter av oklar signifikans analyserat för ddPCR
6. Resultat av regressionsanalyser
Data genererad för "Serial MRD assessment predicts relapse after transplantation in patients with myelodysplastic syndrome"
Keywords: Myelodysplastic-Myeloproliferative Diseases; Myelodysplastiska-myeloproliferativa syndrom; Myelodysplastic syndromes; Myelodysplastiska syndrom; Medical Genetics and Genomics; Medicinsk genetik och genomik; Hematology; Hematologi; Cancer and Oncology; Cancer och onkologi